Experimental investigation on a novel PV-Trombe wall for air heating and purification in the severe cold region - Duan, Xiaojian; Mi, Wensen; Guo, Sen; Shen, Chao; Kalogirou, Soteris A. (My University, 2025)
Trombe wall is a significant contributor to adaptive solar technologies. Enhancing the functionality and efficiency of the Trombe wall is essential to meet the growing energy demands in building applications. This study discusses the development and experimental investigation of a T-wall system designed for severe cold regions. The novel system integrates photovoltaic panels and catalytic oxidation materials, aiming to perform multiple functions simultaneously, i.e., space heating, power generation, and indoor air quality control. The study involves the performance of the novel PV-Trombe wall, the effects of channel spacing and environmental factors. The main findings of this study concern: (1) The novel PV-Trombe wall system demonstrates efficient heating, generating an average of 394.5 kJ of heat per hour. It also produced 0.26 kWh/m2 of electricity daily and significantly improve air sterilization, achieving an average efficiency of 0.384. (2) Channel spacing significantly affects system performance. A 25 cm spacing was identified as optimal, balancing the system's heating, power generation, and sterilization performance effectively. (3) There is a set of optimal environmental factors to maximize the system's performance, highlighting the need to balance environmental factors for optimal system performance.
Keywords: Air heating; Catalytic oxidation; PV-Trombe wall; Renewable energy harvesting; Sterilization